Entre o ordinário e o extra-ordinário : considerações sobre alguns lugares com arte rupestre de tradição esquemática do Norte de Portugal - Sanches, Maria de Jesus (2017)
Within the eld of landscape archaeology, on one hand, and of the fenomenology that complements it, on the other, we will develop an analysis over the role that the places with rupestrian art may have had on the communities that created, maintained and lived in them. To achieve this we will take on as example three cases of places with rupestrian art of schematic tradition of the North of Portugal, dated back to recent pre-history between the 4th and 2nd mill. BC. Taking into account its conguration and topographic location, its patterns, the organization of the motifs etc. we will also support that these places may have had many specic contextual functions; however these can be framed in a wider social function that is the maintenance of cosmologies and of social behaviors, meaning, the naturalization of the norms that support ideology.